Non-invasive ventilation in a pregnancy with severe pneumonia - Mazlan, Mohd Zulfakar; Ali, Saedah; Zainal Abidin, Huda; Mokhtar, Ariffin Marzuki; Ab Mukmin, Laila; Ayub, Zeti Norfidiyati; Nadarajan, Chandran (Elsevier, 2017)
Introduction: Non-invasive ventilation (NIV) is not proven to be effective in treating respiratory failure in severe pneumonia. However, some clinicians nevertheless attempt NIV to indirectly deliver adequate oxygenation and avoid unnecessary endotracheal intubation. Case presentation: In this article, we report the case of a 24-year-old woman at 32 weeks' gestation who presented with hypoxemic respiratory failure requiring mechanical ventilation. She was successfully managed by NIV. Discussion: However, NIV must be managed by providers who are trained in mechanical ventilation. This is of the utmost importance in avoiding any delay should the patient's condition worsen and require endotracheal intubation. Moreover, in pregnant women, the severity of illness may progress quickly due to the immunosuppression inherent in these patients. Conclusion: Special attention should be given to the choices of invasive ventilation and NIV to manage community acquired pneumonia patients in third trimester.